2018
DOI: 10.1002/mrm.27146
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic response function (HRF) variability confounds resting‐state fMRI functional connectivity

Abstract: HRFv, if ignored, could cause identification of false FC. FC findings from HRFv-ignored data should be interpreted cautiously. We suggest deconvolution to minimize HRFv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 47 publications
2
90
0
Order By: Relevance
“…Direct evidence supporting this argument has been offered by studies showing that the vascular response latency identified by a breath-hold task closely resembled the task-evoked hemodynamic delay patterns in primary sensory regions (Chang C et al 2008;Li Y et al 2018). Along similar lines, a recent study observed a marked reduction in the strength of resting-state connectivity if regional HRF shapes were taken into account through blind de-convolution (Rangaprakash D et al 2018), which indeed implies a possible link between regionally varying HRFs and apparent RSN structures reported in the literature, similar to how RRFs/iCRFs determine apparent "physiological" networks reported here.…”
Section: Shared Spatial Patterns Between "Physiological" Dynamics Andsupporting
confidence: 86%
“…Direct evidence supporting this argument has been offered by studies showing that the vascular response latency identified by a breath-hold task closely resembled the task-evoked hemodynamic delay patterns in primary sensory regions (Chang C et al 2008;Li Y et al 2018). Along similar lines, a recent study observed a marked reduction in the strength of resting-state connectivity if regional HRF shapes were taken into account through blind de-convolution (Rangaprakash D et al 2018), which indeed implies a possible link between regionally varying HRFs and apparent RSN structures reported in the literature, similar to how RRFs/iCRFs determine apparent "physiological" networks reported here.…”
Section: Shared Spatial Patterns Between "Physiological" Dynamics Andsupporting
confidence: 86%
“…In addition to connectome specificity, other structural data features may drive functional inter-subject variability including foremost regional variance such as synaptic receptor type and density (39), but also methodological variations such as parcellation differences (3). Notwithstanding, we cannot exclude that the variations in hemodynamic response functions (HRF) across animals and brain location affect SC-FC relations, as it has been shown to contribute to individual variability in human FC estimation (40). In this study we aimed at reducing this variability by scanning awake mice, reducing the confounding effects of anesthesia and allowing collection of data over multiple sessions per mouse (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we aimed at reducing this variability by scanning awake mice, reducing the confounding effects of anesthesia and allowing collection of data over multiple sessions per mouse (41,42). Moreover, we used spin-echo echo planar imaging (EPI), which is more sensitive to microvasculature relative to gradient-echo EPI, especially at high magnetic fields (43), further reducing the variability of HRF (40).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, variable delays between neural activity and peak haemodynamic response around the brain means that temporal precedence in the BOLD response does not necessarily imply neuronal causality. While approaches have been suggested to address this issue [68,69], we instead investigated information-theoretic signatures on simulated neural data, which has a much higher effective sampling frequency than BOLD, and is also relatively unaffected by the temporal convolution that masks neural activity in the BOLD response. In doing so, we highlight important multi-level organisation within the simulated neural time series, in which whole-brain topological signatures (measured using BOLD) overlap with specific signatures of regional (neural) effective connectivity.…”
Section: Discussionmentioning
confidence: 99%